2004
DOI: 10.1289/ehp.6522
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide testing in humans: ethics and public policy.

Abstract: Pesticide manufacturers have tested pesticides increasingly in human volunteers over the past decade. The apparent goal of these human studies is to establish threshold levels for symptoms, termed "no observed effect levels." Data from these studies have been submitted to the U.S. Environmental Protection Agency (EPA) for consideration in standard setting. There are no required ethical guidelines for studies of pesticides toxicity conducted in humans, no governmental oversight is exercised, and no procedures h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…At an expert workshop held during 2002 in New York it was noted that even at that time there were no general ethical guidelines for studies of pesticide toxicity conducted in humans and no governmental oversight. The participants developed several ethical and public policy recommendations regarding human testing of pesticides (Oleskey et al, 2004).…”
Section: Human Studiesmentioning
confidence: 99%
“…At an expert workshop held during 2002 in New York it was noted that even at that time there were no general ethical guidelines for studies of pesticide toxicity conducted in humans and no governmental oversight. The participants developed several ethical and public policy recommendations regarding human testing of pesticides (Oleskey et al, 2004).…”
Section: Human Studiesmentioning
confidence: 99%
“…There currently are no formal guidelines and requirements for ethical conduct in research carried out by private companies. Such companies can provide data to the Environmental Protection Agency (EPA) without adherence to the established ethical standards of research (Oleskey, 2004).…”
Section: A History Of Unethical Research Practicesmentioning
confidence: 99%
“…All these strategies are designed to minimize false positive results while increasing false negatives. For example, in an analysis of ethical and scientific issues associated with industry studies of pesticides on human subjects, the EPA Science Advisory Board found that the industry studies invariably involved sample sizes that were dramatically too small, allowing for huge rates of false negatives (Oleskey et al, 2004).…”
mentioning
confidence: 99%